RELATIONSHIP BETWEEN TRAINING EFFECTIVENESS AND EDUCATOR PERFORMANCE IN THE EASTERN CAPE DEPARTMENT OF EDUCATION, SOUTH AFRICA - ZINDI, Beauty; SIBANDA, Modeni M. (Journal of Social Sciences)
Human Resource Development integrates and aligns training and development with organisational goals and strategy to improve performance. However, ingrained suboptimal skills and training opportunities in the Eastern Cape Department of Education (ECDoE) negatively impacts learning achievement outcomes. The purpose and objective of the study is to establish the relationship between training effectiveness and educator performance in the ECDoE.The study adopts a quantitative research strategy with 270 respondents. A survey questionnaire was used to collect data from participants. The survey questionnaire’s internal consistency and reliability were measured using Pearson's coefficient and Cronbach's alpha, respectively. Results show that most respondents did not view the trainings provided by the ECDoE as relevant to job performance, and the attainment of the Department’s strategic goals. The study concludes that ECDoE’s training should be closely aligned with educators’ Key Performance Areas, Performance Development Plans and individual needs analysis.